Demak Sultanate: The Fortress of Islamic Greatness in the Middle Ages Java Island - Hasyim, Abdul Wahid (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2021)
This article focused on the Demak Sultanate as a stronghold of Islamic greatness in Java island in the Middle Ages. The research used a qualitative method with historical approaches and policy theories. Data collection techniques were done through heuristic stages, internal and external criticism, interpretation, and historiography. The research aimed to answer questions about the historical establishment of the Demak Sultanate and its policies until it became a powerful country and a stronghold of Islamic greatness. This research unveiled important findings. First, Islam, which existed in 1082 on the efforts and struggle of Wali Songo, continued to develop until the Muslim community was formed. Second, the Demak Sultanate, which lasted for almost half a century, was ruled by three sultans; and with their policies, it became a stronghold of Islamic greatness in Java. Third, the Demak Sultanate grew to be an Islamic power center beside Pasai, Malacca, Aceh, Ternate and Tidore. The Demak Sultanate could fend off Portuguese influence which built alliances and conspiracies with the Pajajaran Kingdom in Ujung Barat and Panarukan in the Eastern Edge of Java Island, and Banjarmasin in South Kalimantan, giving rise to the expression of